Protection by ozone preconditioning is mediated by the antioxidant system in cisplatin-induced nephrotoxicity in rats - Aluet Borrego; Zullyt B. Zamora; Ricardo González; Cheyla Romay; Silvia Menéndez; Frank Hernández; Teresita Montero; Enys Rojas (Mediators of Inflammation)
Background: Acute renal failure is a dose-limiting factor of cisplatin chemotherapy. Here, we show the protective effect of ozone oxidative preconditioning against cisplatin-induced renal dysfunction in rats. Ozone oxidative preconditioning is a prophylactic approach, which favors the antioxidant–pro-oxidant balance for preservation of the cell redox state by increasing antioxidant endogenous systems in various in vivo and in vitro experimental models.